2007
DOI: 10.1515/ijpt.2007.17
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Typology of Anglican clergy in England: Diversity, Strengths, and Weaknesses in Ministry

Abstract: Recent research within the psychology of religion and empirical theology has drawn attention to the theoretical and practical power of psychological type theory to illuminate and to facilitate the practice of Christian ministry. Building on this tradition, in the present study the psychological type preferences of 626 male Anglican clergy and 247 female Anglican clergy in England were assessed using the Myers-Briggs Type Indicator. The purpose was to profile the personal and professional qualities of those eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
109
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(123 citation statements)
references
References 0 publications
14
109
0
Order By: Relevance
“…The core information is found in the section on dichotomous preferences, showing preferences for introversion (60%) over extraversion (40%), for intuition (55%) over sensing (46%), for feeling (57%) over thinking (43%) and for judging (76%) over perceiving (24%). These findings are basically in line with the normative data provided by Francis, Craig, Whinney, Tilley, and Slater (2007). In this sense clergy in the Diocese of Chester are typical of the psychological type profile of clergy within the Church of England as a whole.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The core information is found in the section on dichotomous preferences, showing preferences for introversion (60%) over extraversion (40%), for intuition (55%) over sensing (46%), for feeling (57%) over thinking (43%) and for judging (76%) over perceiving (24%). These findings are basically in line with the normative data provided by Francis, Craig, Whinney, Tilley, and Slater (2007). In this sense clergy in the Diocese of Chester are typical of the psychological type profile of clergy within the Church of England as a whole.…”
Section: Resultssupporting
confidence: 89%
“…In a second study, drawing on data from 622 clergymen, Francis, Robbins, Duncan, and Whinney (2010) found very similar results. Parallel studies, drawing on data from clergywomen reported by Francis, Craig, Whinney, Tilley, and Slater (2007) found that the differences in psychological type profile between clergymen and clergywomen were much smaller than the differences found among men and women in the wider population (Kendall, 1998).…”
Section: Psychological Typementioning
confidence: 98%
See 2 more Smart Citations
“…The first step in data analysis examined the scale properties of the eight scales Indicator and reported in Francis, Craig, Whinney, Tilley, and Slater (2007). On the other hand, such a clear preference for extraversion was not found in this earlier study.…”
Section: Resultsmentioning
confidence: 55%